Study On Antimicrobial Activity And Combination Effects Of Polygonum Minus - Khadija Zedan Hassan
ABSTRACT Antimicrobial activities of aqueous, methanol and ethanol extracts from Polygonum minus were evaluated against six strains of Gram positive and Gram negative bacteria, including Bacillus subtilis, Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium and Serratiamarcescens by agar-well diffusion assay and microdilution test. The agar-well diffussion assay was carried out to identify the antimicrobial susceptibility, while the microdilution test was done to determine the minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC). Generally, P. minus ethanol, methanol and aqueous extracts showed a broad spectrum of antimicrobial activity on the tested bacteria. In agar-well diffusion test, the range of inhibition zone produced was between 6 mm to 13.5 mm in diameter. In microdilution assay, high inhibition effect with the lowest MIC value (62.50 mg/ml) showed by aqueous extracts towards S. typhimurium and B. subtilis, methanol extracts towards B. subtilis as well as ethanol extracts towards S. aureus, S. epidermidis and S. typhymurium. The aqueous and methanol extracts also exhibited a bactericidal effect towards all six strains of bacteria. However, ethanol extracts could only kill five bacterial strains, including B. subtilis, S. aureus, S. typhimurium, S. epidermidis and S. marcescens. In general, all test bacteria were susceptible to P. minus aqueous, methanol and ethanol extracts, except S. typhimurium whose MBC/MIC value was greater than 4 (>4) towards ethanol extracts. In combination study, the methanol and ethanol extracts from P. minus were combined with Streptomycin sulfate. The combination effects of P. minus methanol extracts with Streptomycin sulfate against B. subtilis showed that about 16.7% were synergy (two out of 12 combinations), 16.7% were additive (two out of 12 combinations) and 66.7% were indifferent (eight out of 12 combinations). Meanwhile, the combination effects between P. minus ethanol extract with Streptomycin sulfate against B. subtilis indicated that about 50% (six out of 12 combinations) were antagonistic, 16.67% (two out of 12 combinations) were indifferent and 33.33 % (four out of 12 combinations) were additive.